2012
DOI: 10.1007/s00213-012-2885-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sedative antidepressants on prefrontal cortex activity during verbal fluency task in healthy subjects: a near-infrared spectroscopy study

Abstract: Administration of mirtazapine for eight consecutive days affected oxy-Hb changes on NIRS. This result indicates that researchers should consider how certain types of antidepressant could influence brain function when the brain activity of patients with psychiatric disorders is assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 28 publications
4
13
1
Order By: Relevance
“…For example, Kohmura et al (2013) examined the effects of sedative antidepressants on NIRS signals in a randomized controlled trial. They found that the administration of mirtazapine (15 mg for 8 consecutive days) increased [oxy-Hb] values during VFT, whereas trazodone (25 mg for 8 days) and a placebo did not have any significant effects on NIRS signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Kohmura et al (2013) examined the effects of sedative antidepressants on NIRS signals in a randomized controlled trial. They found that the administration of mirtazapine (15 mg for 8 consecutive days) increased [oxy-Hb] values during VFT, whereas trazodone (25 mg for 8 days) and a placebo did not have any significant effects on NIRS signals.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies including healthy volunteers have shown the significant effects of antidepressants on NIRS signals (Tsujii et al, 2007, Tsujii et al, 2009, Kohmura et al, 2013), although studies including patients with psychiatric disorders have shown inconsistent results (Noda et al, 2012, Takizawa et al, 2014). Moreover, investigations of the effects of other psychotropic drugs, such as benzodiazepines and antipsychotics, on NIRS signals are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Second, in this study, 13 subjects were taking psychotropic medications. Given that antidepressants have been reported to affect hemodynamic responses,37 a medication effect cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that acetylcholine-esterase inhibitors influence neurovascular coupling [47]. Other studies have reported that administration of antidepressants have influence on [oxy-Hb] changes [48-50]. However, a review of neuroimaging studies on bipolar disorder by Phillip et al [51] reported neither significant nor ameliorative effects of psychotropic medications on abnormal structural and functional neuroimaging measures.…”
Section: Discussionmentioning
confidence: 99%